2022
DOI: 10.1186/s12951-022-01587-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound/nanomechanical force generators enhance osteogenesis of BMSCs through microfilaments and TRPM7

Abstract: Background Low-intensity pulsed ultrasound (LIPUS) has been reported to accelerate fracture healing, but the mechanism is unclear and its efficacy needs to be further optimized. Ultrasound in combination with functionalized microbubbles has been shown to induce local shear forces and controllable mechanical stress in cells, amplifying the mechanical effects of LIPUS. Nanoscale lipid bubbles (nanobubbles) have high stability and good biosafety. However, the effect of LIPUS combined with function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 68 publications
(72 reference statements)
3
23
0
Order By: Relevance
“…The stress induced by mechanical forces results in the formation of thick actin bundles, which was also confirmed in this study after the FLIPUS stimulation ( Figure 7 a,b). The polymerization of actin fibers after ultrasound stimulation is in agreement with previous reports [ 32 , 47 ]. The expression of vinculin, which is an important linker in the focal adhesion complex, bridging actin with integrin receptors bound to the surrounding matrix, was not affected by the stimulation.…”
Section: Discussionsupporting
confidence: 93%
“…The stress induced by mechanical forces results in the formation of thick actin bundles, which was also confirmed in this study after the FLIPUS stimulation ( Figure 7 a,b). The polymerization of actin fibers after ultrasound stimulation is in agreement with previous reports [ 32 , 47 ]. The expression of vinculin, which is an important linker in the focal adhesion complex, bridging actin with integrin receptors bound to the surrounding matrix, was not affected by the stimulation.…”
Section: Discussionsupporting
confidence: 93%
“…Zhang et al uncovered that the addition of magnesium ions throughout the bone tissue engineering process is beneficial to the bone formation ability of BMSCs (Xiong et al, 2020;Zhang et al, 2019). Yao et al discovered that the osteogenic potential of BMSCs could be enhanced by nanomicrofilaments (Yao et al, 2022). These investigations revealed that biomaterials might increase the therapeutic efficiency of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al. discovered that the osteogenic potential of BMSCs could be enhanced by nano‐microfilaments (Yao et al., 2022). These investigations revealed that biomaterials might increase the therapeutic efficiency of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In MC3T3-E1 cells, both receptors appear to be functional in the osteoblastic mechano-transduction that results in reduced proliferation [ 66 ]. TRPM7 is also a common target for mechanical loading to stimulate bone formation, as results obtained in various models suggest [ 67 , 68 , 69 ]. TRPM7 is critically important in bone formation [ 70 ].…”
Section: Ion Channels Involved In Progenitor Cell Differentiationmentioning
confidence: 99%